OPPORTUNITIES FOR ADAPTING INTERNATIONAL EXPERIENCE IN COMBATING BULLYING IN THE CONTEXT OF IMPROVING KAZAKHSTAN'S LEGISLATION (Journal of actual problems of jurisprudence, 2026)
The issue of bullying remains one of the most pressing and attention-worthy challenges in modern society. This study focuses on analyzing the experience of combating bullying in countries such as Japan, South Korea, and the Philippines. The authors explored the possibilities of adapting this experience in the context of improving Kazakhstan's legislation. Based on the study of international practices and standards in the fight against bullying, key approaches were identified that could be beneficial for integration into Kazakhstan’s legal and educational systems. The study emphasizes the necessity of not only introducing a clear legal definition of bullying but also establishing adequate legal measures to hold perpetrators accountable. The research relies on comparative legal and analytical approaches, including an analysis of legislation and practices in foreign countries, as well as assessing their applicability to the Kazakhstani context. The results obtained hold both scientific and practical significance, as they provide concrete recommendations for developing regulatory acts and educational programs aimed at reducing the level of bullying in the country. The contribution of this study lies in its proposals for improving legislative and organizational measures to counter bullying, thereby protecting the rights of children and vulnerable groups in accordance with international standards.Key words: bullying, harassment, countering bullying, legislation, Kazakhstan, international experience.